Evolution of Shader Technology: From Fixed Pipeline to Real-Time Ray Tracing, A Case Study on Racing Games - Feng, Yujie (Transactions on Computer Science and Intelligent Systems Research, 2025)
This study examines the evolution of shader technologies in racing games, focusing on their impact on visual fidelity, performance, and user experience. The research highlights how these innovations have transformed the graphics landscape in racing simulations by exploring the development of various shader frameworks, such as fixed-function pipelines, programmable pipelines, and real-time ray tracing. The findings reveal that advanced visual effects significantly enhance player immersion and realism and introduce performance optimization and hardware dependency challenges. The study also addresses how different technologies can affect gameplay fluidity, particularly in resource-intensive scenarios. Future research directions are proposed, including exploring optimization techniques, integrating artificial intelligence for adaptive performance, and cross-platform compatibility. Additionally, the potential applications of shader technologies in emerging fields like virtual reality, augmented reality, and driving simulators are discussed. Overall, this study underscores the pivotal role of shader technologies in shaping the future of racing games and simulations.